Ethics and deontology in advertising. Nike 'Dream Crazier' 2019 as a feminist campaign at Instagram - Padilla Castillo, Graciela; Presol Herrero, África (Comunicación y Género [Communication and Gender], 2020)
This research studies the Nike Dream Crazier 2019 campaign, on Instagram, in the first month of its release. A double methodology is established: a longitudinal bibliographical exploration, which reflects on ethics and deontology, on sexist advertising, and the main investigations that define the phenomenon; and a correlational inquiry, which measures virality on Instagram, through the hashtag #DreamCrazier and the 10 most influential users, according to the Keyhole software. The results show that influencers are unknown women, who use a simple language, loaded with hashtags and emojis, which reduce the language barrier. They become the paradigm of cultural produsage, being users of the brand and producing positive advertising contents that spread throughout the world.
Keywords: Advertising; ethics; Instagram; hashtags; female sport